2006
DOI: 10.1111/j.1365-246x.2006.02905.x
|View full text |Cite
|
Sign up to set email alerts
|

Inversion of the HZ ratio of microseisms forS-wave velocity in the crust

Abstract: S U M M A R YS-wave velocity in the shallow crust is an important controlling parameter for ground motion amplification. It is a key parameter for prediction of ground motion and thus for earthquake hazard mitigation in general. Shallow S-wave velocity structure has often been obtained from phase velocity of microtremors and microseisms. We present a new approach which directly inverts the ratio of horizontal to vertical amplitudes of microseisms which is referred to as the HZ ratio in this paper. Our approach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
39
1
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(41 citation statements)
references
References 28 publications
0
39
1
1
Order By: Relevance
“…Two distinctive dispersive waves, namely fundamental and higher-mode Rayleigh waves, are observed in the beamformed data. This result differs from those of other studies of double-wave-frequency microseisms, which have shown the noise field to be dominated by a single mode, namely fundamental mode Rayleigh waves [Lacoss et al, 1969;Tanimoto and Alvizuri, 2006]. The dominant source regions of the two signals we observe are interpreted with reference to New Zealand's oceanographic conditions.…”
Section: Introductioncontrasting
confidence: 56%
“…Two distinctive dispersive waves, namely fundamental and higher-mode Rayleigh waves, are observed in the beamformed data. This result differs from those of other studies of double-wave-frequency microseisms, which have shown the noise field to be dominated by a single mode, namely fundamental mode Rayleigh waves [Lacoss et al, 1969;Tanimoto and Alvizuri, 2006]. The dominant source regions of the two signals we observe are interpreted with reference to New Zealand's oceanographic conditions.…”
Section: Introductioncontrasting
confidence: 56%
“…Recently, Tanimoto and Alvizuri (2006) and Hobiger et al (2009) proposed to extract the ellipticity of Rayleigh waves from NHV curves by a random decrement technique. This might in turn be used as input for the inversion analyses to estimate the S-wave velocity profiles.…”
Section: Nhv Inversionmentioning
confidence: 99%
“…The subscripts sw, zh, and rf in all equations represent dispersion, ZH ratio, and RF data, respectively; r sw ; r zh ; r rf are the corresponding residual data vectors for different datasets; G sw ; G zh ; G rf are the corresponding partial derivative matrices, which can be calculated numerically through difference algorithms (e.g., Julià et al 2000;Tanimoto and Alvizuri 2006;Julià 2007). Instead of inverting three datasets at the same time, we propose a stepwise joint inversion strategy for better taking advantages of their complementary sensitivities to the v S structure.…”
Section: Methodsmentioning
confidence: 99%
“…Joint surface wave tomography with both earthquake surface waves and ambient noise cross-correlation can successfully characterize crustal and upper mantle structure (e.g., Yao et al 2008Yao et al , 2010. Studies have also shown that the vertical and horizontal components of fundamental mode Rayleigh waves have a 90°phase shift, and their amplitude ratio (ZH ratio or ellipticity) is frequency dependent and only controlled by the structure beneath the recorded seismic station (Tanimoto and Alvizuri 2006;Tanimoto and Rivera 2008) under the 1D layered model assumption. Rayleigh wave ZH ratio has higher sensitivity to shallower structures compared to Rayleigh wave dispersion at the same period .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation